Impact of Calibrating Public Accountability (CPA) Model and Utilization of Quality of Management Accounting Information Systems on School Organizational Performance: Survey on Private Schools in Cimahi City - Siti Kustinah; Muhammad Anggionaldi (International Journal of Science and Society, 2022)
Education is important for the progress and prosperity of the nation and state. Through education, competent and reliable human resources will be born. Minister of Education and Culture Research and Technology Nadiem Makarim in November 2019 mentioned the importance of character education in the midst of the large role of technology today. Character education will be the foundation for the nation's successors to survive and thrive in the current era of digitalization. Continuing education must be supported by safe conditions, situations and conditions. But now, especially in the past few years, the pandemic has had another effect on the world of education. The effect of this pandemic also has an impact on the achievement of performance in schools, especially schools with private status. This decline in the performance of private schools can be caused by accountability in presenting their financial statements and the use of accounting information systems. The purpose of this study was to find out how the description of accountability in private schools using accountability measurements based on Calibrating Public Accountability, description of the use of management accounting information systems, descriptions of school organizational performance and how accountability and utilization of management accounting information systems influence school organizational performance, either partially or partially. simultaneous. Based on the results of the study, it shows that the accountability variable is in very good condition. The variable utilization of accounting information systems in private schools in Cimahi City is in good condition.